2021
DOI: 10.1055/a-1400-2668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment Adherence on Quality of Life in Hypoparathyroid Patients

Abstract: Objectives This study aimed to evaluate the current situation of hypoparathyroid patients and to investigate the relationship between treatment adherence and quality of life. Study design Prospective, multicentre study. Methods Adult patients presenting with the diagnosis of hypoparathyroidism to 20 different endocrinology clinics were included. They were receiving con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The observation indicators are divided into the following steps: (1) General Self-efficacy Scale (GSES) is used at all 4 time points to evaluate the patients' self-efficacy. The full score was 40, and self-efficacy increased with the increase of the score; (2) the patient's adherence is evaluated according to the Morisky Medication Adherence Scale (MMAS-8) [ 15 ]. The first seven adherence items all contain yes and no, each of which is scored in accordance with 0∼1 points.…”
Section: Clinical Treatment Methods and Evaluation Indicatorsmentioning
confidence: 99%
“…The observation indicators are divided into the following steps: (1) General Self-efficacy Scale (GSES) is used at all 4 time points to evaluate the patients' self-efficacy. The full score was 40, and self-efficacy increased with the increase of the score; (2) the patient's adherence is evaluated according to the Morisky Medication Adherence Scale (MMAS-8) [ 15 ]. The first seven adherence items all contain yes and no, each of which is scored in accordance with 0∼1 points.…”
Section: Clinical Treatment Methods and Evaluation Indicatorsmentioning
confidence: 99%
“…Calcitriol has actually been linked to declining renal function and risk for polyuria and nephrolithiasis [22][23][24][25]. Coming back to poor biochemical control of our patients, one must keep in mind that it is clearly linked to a higher risk for complications and worse quality of life as reported elsewhere [25][26][27].…”
Section: Discussionmentioning
confidence: 85%
“…The Morisky Medication Adherence Scales measure patients' cooperation (adherence) in their medication (55).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, hormone levels should be carefully monitored, which requires cooperation from the patient. Therefore, it is important to inform patients about their health status to ensure adherence (33,54,55). Indeed, a recent study has shown that non-adherent thyroid patients reported more symptoms of depression, anxiety, and poorer quality of life (55).…”
Section: Adherencementioning
confidence: 99%
See 1 more Smart Citation